PEMANFAATAN APLIKASI QASIR SEBAGAI UPAYA DIGITALISASI PENCATATAN KEUANGAN PADA USAHA RUMAHAN HAPPYNEST DESSERT DI KOTA BIMA - Ita Purnama; Nurrizah Syaputri; Gunawan Sakti; Ikko Apriyan (CV. Denasya Smart Publisher, 2026)
Micro, small, and medium-sized enterprises (MSMEs) play a vital role in boosting the local economy. However, many MSME owners still face challenges in financial management, particularly in recording transactions and monitoring business revenue. Happynest Dessert is a home-based culinary business that still records transactions manually, resulting in suboptimal financial management. This community service activity aims to assist with the digitization of financial record-keeping through the use of the Qasir app. Implementation methods includeobservation, interviews, outreach, guidance on app usage, and evaluation. The results of the activity show that the Qasir app helps business owners record daily transactions in a more structured manner, monitor revenue automatically, and facilitate the evaluation of business progress. Thus, the use of the Qasir app can better support the effectiveness of financial management in MSMEs.